Analisis Potensi Dan Prioritas Pengembangan Pariwisata Di Kota Serang Provinsi Banten - Putra, Zandy Pratama, Dr. Kuswaji Dwi Priyono, M.Si, Hj.Umrotun M.Si (2017)
This research aims to: (1) to know and analyze classification of internal and external potencies of tourism aspect in Serang City (2) to know and analyze region that have the highest potential of tourism to be developed in Serang. The research used survey method, namely making a direct observation in field using observation sheet and interview with visitors of tourism objects, which is using questionnaire. According to the potency of internal and external analysis showed that Masjid Agung Banten (Great Mosque of Banten) and Banten Lama (Old Banten) gain high potential in external and internal, so was like Keraton Surosowan and Water Boom Tembong Jaya. Speelwijk Fortress and Pulau Dua Nature Preservation gain medium value of internal and external. While for Pasir Putih Beach and Ki Mas Jong Cave gain low value of internal and external. From eight of tourism object, Masjid Agung Banten (Banten Great Mosque) have the first priority in tourism, followed by Banten Lama (Old Banten) and Keraton Surosowan, Water Boom Tembong Jaya, Speelwijk Fortress, Pulau Dua Nature Preservation, Pasir Putih Beach, and Ki Mas Jong Cave. The development of tourism object could be done by maximizing quality of tourism object by completing and revitalizing the facility which began to break down and it goes with routine maintenance of structure and infrastructure and do cooperation between government and tourism object party.